(untitled) (Acta Scientiarum. Biological Sciences, 2018)
Consuming raw food like lettuce may carry protozoa cysts and helminth eggs, causing parasitic infections. Therefore, the parasitological analysis of this type of food it’s important for public health because it provides data on the hygiene conditions in which these vegetables were produced, transported, processed and handled until the ingestion. This study aimed to evaluate the occurrence of parasitic structures in samples of lettuce (Lactuca sativa) sold in self-service restaurants in São Miguel do Oeste, Santa Catarina State, Brazil. The samples were randomly collected in 20 locations in duplicate, prepared according to the method of Hoffman, Pons, and Janer (1934) and analyzed with an optical light microscopy. The parasitic structures found were Cysts Balantidium coli, Giardia spp. and Entamoeba spp. Ascaris lumbricoides eggs and grubs of Strongyloides stercoralis. These results demonstrate that the lettuce served at most self-service restaurants evaluated is unfit for intake and indicates the need to implement hygienic and educational measures to minimize contamination and ensure the safety of the ingestion of this vegetable.